2022
DOI: 10.3390/jzbg3020018
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Zoo-Housed Red Pandas (Ailurus fulgens): A Case-Study Testing the Behavioural Variety Index

Abstract: The red panda is listed as “endangered” in the IUCN Red List of Threatened Species, due to the rapid population decline. Improving our knowledge on the red panda biology and ethology is necessary to enhance its husbandry and breeding in zoos. Behavioural variety, intended as the presence of a wide array of species-specific behaviour, has been considered a positive welfare index in zoo-housed animals. The aim of this study was to describe the behaviour of two pairs of zoo-housed red pandas, one of them with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Studies of wild red panda observe active activity 45-60% of the time, dependent on season [16,18], whereas our study shows panda to be less active (19-36%). A more recent study [29] found captive red panda at Rotterdam Zoo to be active 40-53% of the time, although the two pairs in the study were young breeding pairs, and perhaps best compared to the pair at Auckland Zoo (Khela and Ramesh). In captivity, panda are brought a selection of food, such as bamboo, fruits, specialised biscuits, and the occasional day-old chick or mouse.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Studies of wild red panda observe active activity 45-60% of the time, dependent on season [16,18], whereas our study shows panda to be less active (19-36%). A more recent study [29] found captive red panda at Rotterdam Zoo to be active 40-53% of the time, although the two pairs in the study were young breeding pairs, and perhaps best compared to the pair at Auckland Zoo (Khela and Ramesh). In captivity, panda are brought a selection of food, such as bamboo, fruits, specialised biscuits, and the occasional day-old chick or mouse.…”
Section: Discussionmentioning
confidence: 67%
“…Pasang would sleep from 1900 to the early morning hours when he would scent mark before keepers arrived. Scent marking and other exploratory/territorial behaviours are considered positive indicators of red panda health in captivity [29]. This bimodal pattern of activity during the day clearly followed keeper timings.…”
Section: Discussionmentioning
confidence: 99%
“…The most common method of behavioral diversity assessment was the Shannon–Wiener index with 79 individual species studied using this method, with behavioral richness (the number of behaviors observed) also appearing commonly (31 species studied) ( Table 1 ). The Behavioral Variety index (proportion of behaviors seen in captive, versus wild animals) featured in two papers [ 20 , 21 ].…”
Section: Summary Of Behavioral Diversity Literaturementioning
confidence: 99%
“…The Behavioral Variety index (BVI) features in some animal behavior literature (e.g., 20,21), and has some potential in investigating animal welfare. BVI requires a full ethogram of an animal its ‘natural’ state to determine the range of behaviors it may express [ 20 , 21 ]. These behaviors are then categorized into groups—such as social behavior.…”
Section: Tools To Measure Behavioral Diversitymentioning
confidence: 99%
See 1 more Smart Citation